Gender as a Moderator: Understanding Cross-gender Brand Extensions through the Lens of Social Identity Theory - Veena Prasad Vemuri (New Advances in Business, Management and Economics Vol. 7, 2025)
This chapter explores the complex interrelationship between gender identity and brand extension processes in contemporary consumer behaviour. Through an integrative theoretical framework, we examine how gender-specific cognitive processing styles, category boundary flexibility, risk perception patterns, and social identity considerations influence consumers’ receptiveness to brand extensions across product categories. Our analysis reveals that female consumers typically demonstrate more flexible brand generalisation tendencies, while male consumers often apply stricter category-based criteria, particularly when extensions cross gender boundaries. Drawing on social identity theory and recent advances in gender research, we develop a multi-dimensional model of gender’s moderating effects on brand generalisation and propose methodological approaches for empirical investigation. The chapter concludes with strategic implications for managing cross-gender brand extensions in an evolving marketplace where traditional gender boundaries are increasingly fluid. This research contributes to a more nuanced understanding of how gender shapes consumer-brand relationships and offers practical guidance for gender-sensitive brand extension strategies.